Fandom

Math Wiki

Constant derivative rule/Proof

1,078pages on
this wiki
Add New Page
Talk0 Share

\frac{d}{dx}a=0, for some constant a.

Prerequisites

The limit definition of the derivative, f'(x)=\lim_{h \to 0}\frac{f(x+h)-f(x)}{h}

Proof

Let f(x) = a for some constant a. From the limit definition of the derivative:

f'(x)=\lim_{h \to 0}\frac{f(x+h)-f(x)}{h}
f'(x)=\lim_{h \to 0}\frac{a-a}{h}
f'(x)=0

QED

Ad blocker interference detected!


Wikia is a free-to-use site that makes money from advertising. We have a modified experience for viewers using ad blockers

Wikia is not accessible if you’ve made further modifications. Remove the custom ad blocker rule(s) and the page will load as expected.

Also on Fandom

Random Wiki